High-filling nano-starch modified PHB material and preparation method thereof

By nano-sizing and modifying natural potato starch, highly filled nano-starch modified PHB material is prepared, which solves the problems of high cost and poor processing performance of PHB material, achieves high strength, toughness and biodegradability, and expands the application field.

CN120842816APending Publication Date: 2025-10-28QINGDAO GON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511006861.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

The high cost and poor processing performance of existing PHB materials limit their large-scale application, and the mechanical properties are reduced after high starch filling, so the problems of compatibility and mechanical properties need to be solved.

Method used

Highly filled nano-starch modified PHB material was prepared by nano-processing natural potato starch and using methods such as silane modification and polyethylene glycol modification. The material was then melt-blended using a twin-screw extruder to form a homogeneous material.

Benefits of technology

While maintaining high strength and toughness, the material has excellent biodegradability and is suitable for food packaging, agriculture and medical fields, expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120842816A_ABST
    Figure CN120842816A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer modification, in particular to a highly-filled nano-starch modified PHB material and a preparation method thereof.The highly-filled nano-starch modified PHB material is prepared from, by mass, 70-90 parts of PHB resin, 10-30 parts of modified starch based on natural potato starch, 0.1-0.5 part of main antioxidant and 0.1-0.5 part of auxiliary antioxidant, and under the testing condition of 180 DEG C * 2.16 kg, the content of the nano-starch modified PHB material is larger than that of the PHB resin. The melt flow rate is 1-10 g / 10 min, and the particle size of the natural potato starch is 30-50 [mu] m. The PHB material prepared by the preparation method disclosed by the invention can maintain relatively high toughness on the premise of high strength, and has excellent biodegradability at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer modification, specifically to a highly filled nano-starch modified PHB material and its preparation method. Background Technology

[0002] Polyhydroxybutyrate (PHB) is a natural high-molecular-weight polymer with unique properties such as biocompatibility, biodegradability, non-irritation, non-immunogenicity, and tissue compatibility. It has been successfully applied in tissue engineering, drug delivery systems, orthopedics, and surgical sutures. PHB exhibits excellent biodegradability; its decomposition products are entirely bioavailable and cause no environmental pollution. Its physical properties and molecular structure are very similar to polypropylene, such as molar mass, softening point, crystallinity, and tensile strength. Currently, it is mainly used in medical, industrial, packaging, and agricultural fields.

[0003] Although PHB (polyhydroxybutyrate) is a biodegradable material with green and environmentally friendly properties, its high cost and poor processing performance limit its large-scale application. Blending it with starch can significantly reduce material costs and improve some processing properties, but it also introduces new challenges.

[0004] The introduction of low-cost starch significantly lowers the economic barrier for PHB, making it more suitable for large-scale environmentally friendly substitution. However, issues such as compatibility and reduced mechanical properties still need to be addressed.

[0005] Therefore, developing a PHB / starch material with high starch content and high mechanical properties is of great significance. Summary of the Invention

[0006] To address the problems existing in the prior art, the purpose of this invention is to provide a highly filled nano-starch modified PHB material that maintains high mechanical properties while possessing high starch content, making it suitable for food packaging, agriculture, and medical applications.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is: a highly filled nano-starch modified PHB material, comprising, by weight: 70-90 parts by weight of PHB resin, 10-30 parts by weight of modified starch based on natural potato starch, 0.1-0.5 parts by weight of primary antioxidant, and 0.1-0.5 parts by weight of secondary antioxidant. The PHB resin has a melt flow rate of 1-10 g / 10 min under the test conditions of 180 ℃ × 2.16 kg, and the natural potato starch has a particle size of 30-50 μm.

[0008] The aforementioned highly filled nano-starch modified PHB material, wherein the modified starch is nano-sized starch SNPs, the particle size of the SNPs is less than or equal to 0.1 μm, and the preparation method of the SNPs includes: Step 1: Add natural potato starch and anhydrous ethanol to the grinding jar of a planetary ball mill at a ratio of 1:2, add 5% surfactant OP-10, maintain a fixed rotation speed of 300-500 r / min, control the temperature not to exceed 35 ℃, and the humidity not to exceed 40%; Step 2: The starch obtained in Step 1 is subjected to multiple ultrasonic centrifugations with ethanol to remove surfactants and soluble starch. Then, the ultrasonically centrifuged starch is placed in a vacuum oven at 50 °C for 12 h to remove all moisture and ethanol, thus obtaining nano-sized starch SNPs.

[0009] The above-mentioned highly filled nano-starch modified PHB material, wherein the modified starch is silane-modified nano-starch SNPs-O, and the silane-modified nano-starch SNPs-O is graft-modified nano-starch, is prepared by the following steps: Step 3-1: Dry the nano-sized starch SNPs at 60 °C for 12 hours to remove moisture, then disperse them in anhydrous ethanol and sonicate for 30 minutes to activate the hydroxyl groups. Step 4-1: Dissolve 2% starch by weight of octadecyltrimethoxysilane ODS in 9:1 ethanol / water, add acetic acid to adjust the pH to 4-5, and magnetically stir at 60 °C for 30 minutes to generate silanol; Step 5-1: Add silanol to the starch suspension and react for 6 hours under nitrogen protection at 80 °C, maintaining the pH at 4-5. Cool to room temperature and perform multiple ultrasonic centrifugations on the obtained starch with ethanol to remove the remaining solvent and a small amount of soluble starch. Then place it in a vacuum oven at 50 °C for 12 hours to remove all moisture and ethanol, thus obtaining silane-modified nano starch SNPs-O.

[0010] The above-mentioned highly filled nano-starch modified PHB material, wherein the modified starch is plasticized starch TPSNPs-O, and the plasticized starch TPSNPs-O is a thermoplastic starch obtained by plasticizing silane-modified nano-starch SNPs-O, is prepared by the following method: Step 6-1: Dry the silane-modified nano starch SNPs-O at 60-80 ℃ until the moisture content is <5%; Step 7-1: Mix the dried silane-modified nano starch SNPs-O and plasticizer evenly in a high-speed mixer; Step 8-1: The material is melt-blended using a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, plasticized starch TPSNPs-O is obtained.

[0011] The above-mentioned highly filled nano-starch modified PHB material, wherein the modified starch is polyethylene glycol modified nano-starch SNPs-P, and the polyethylene glycol modified nano-starch SNPs-P is graft-modified nano-starch, is prepared by the following steps: Step 3-2: Disperse nano-sized starch SNPs in water, add sodium periodate (NaIO4) with a starch mass fraction of 20%, and stir at 25 ℃ for 6 hours to generate aldehyde-modified starch; Step 4-2: The obtained aldehyde-modified starch is subjected to multiple ultrasonic centrifugations with ethanol to remove the remaining solvent and a small amount of soluble starch, and then cooled and dried. Step 5-2: Prepare a reaction solution by mixing aldehyde-modified starch after ultrasonic centrifugation, PEG-20000, and DMSO in a ratio of 1:1:10. Add citric acid with a starch mass fraction of 10% and react at 80 °C for 4 hours under nitrogen atmosphere to remove free PEG. Freeze-dry to obtain polyethylene glycol modified nano starch SNPs-P.

[0012] The above-mentioned highly filled nano-starch modified PHB material, wherein the modified starch is plasticized starch TPSNPs-P, and the plasticized starch TPSNPs-P is a thermoplastic starch obtained by plasticizing polyethylene glycol modified nano-starch SNPs-P, the preparation method includes: Step 6-2: Dry the polyethylene glycol-modified nano starch SNPs-P at 60-80 ℃ until the moisture content is <5%; Step 7-2: Mix the dried starch SNPs-P and plasticizer evenly in a high-speed mixer; Step 8-2: The material is melt-blended using a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, plasticized starch TPSNPs-P is obtained.

[0013] A method for preparing a highly filled nano-starch modified PHB material includes the following steps: Step a: Weigh and dry the PHB resin, modified starch based on natural potato starch, main antioxidant, and auxiliary antioxidant according to the specified ratio; Step b: After mixing the dried raw materials from step a, continuously and evenly add them to the main feed cylinder of the twin-screw extruder. After the extruded strip is cooled by a water tank, it is granulated to obtain highly filled nano-starch modified PHB material.

[0014] The above-mentioned method for preparing highly filled nano-starch modified PHB material uses at least one of the following: nano-starch SNPs, silane-modified nano-starch SNPs-O, plasticized starch TPSNPs-O, polyethylene glycol-modified nano-starch SNPs-P, and plasticized starch TPSNPs-P.

[0015] In the above-mentioned method for preparing highly filled nano-starch modified PHB material, the twin-screw extruder has a rotation speed of 350-500 rpm, a screw diameter of 30-65 mm, and an aspect ratio (L / D) of 25-28.

[0016] In the above-mentioned method for preparing highly filled nano-starch modified PHB material, the temperatures of the conveying section, melting section, mixing section, homogenizing section, and die section of the twin-screw extruder are 140-150 ℃, 150-165 ℃, 155-175 ℃, 150-160 ℃, and 145-155 ℃, respectively.

[0017] The beneficial effects of the high-filled nano-starch modified PHB material and its preparation method proposed in this invention are as follows: The preparation method of the high-filled nano-starch modified PHB material proposed in this invention is relatively simple and can be stably mass-produced. By nano-processing natural potato starch, the particle size of natural potato starch is reduced. Further modification of the nano-starch yields silane-modified nano-starch SNPs-O or polyethylene glycol-modified nano-starch SNPs-P to improve the compatibility between starch and PHB material. To facilitate compounding with PHB, the modified starch is prepared as thermoplastic starch to further enhance the interfacial bonding between the two.

[0018] The PHB material prepared by this invention maintains high strength and toughness while exhibiting excellent biodegradability, making it suitable for food packaging, agriculture, and medical fields. It greatly improves the problem of limited application caused by the high brittleness and cost of PHB materials, and is of great help in expanding its application fields. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of ball milling in an embodiment of the present invention. Detailed Implementation

[0020] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described below in conjunction with specific embodiments and accompanying drawings.

[0021] Example 1 A highly filled nano-starch modified PHB material comprises, by weight: 70-90 parts PHB resin, 10-30 parts modified starch based on natural potato starch, 0.1-0.5 parts main antioxidant, and 0.1-0.5 parts auxiliary antioxidant. Under test conditions of 180 ℃ × 2.16 kg, the melt flow rate of the PHB resin is 1-10 g / 10 min, and the particle size of the natural potato starch is 30-50 μm.

[0022] Specifically, the modified starch based on natural potato starch uses at least one of nano-sized starch SNPs, silane-modified nano-sized starch SNPs-O, plasticized starch TPSNPs-O, polyethylene glycol-modified nano-sized starch SNPs-P, and plasticized starch TPSNPs-P.

[0023] Nanoscale fractionated starch (SNPs) are nanoscale starch particles with a particle size of less than or equal to 0.1 μm, and the preparation method is as follows.

[0024] Nano-starch particles were prepared using a planetary ball mill. The ball milling mechanism is explained as follows: Figure 1 As shown, natural potato starch and anhydrous ethanol were added to a ball mill jar at a ratio of 1:2. 5% surfactant OP-10 was added to prevent starch sedimentation. The rotation speed was fixed at 300-500 r / min, and the temperature was controlled below 35 ℃ and the humidity below 40%.

[0025] The obtained starch was subjected to multiple ultrasonic centrifugations with ethanol to remove surfactants and a small amount of soluble starch. Then, it was dried in a vacuum oven at 50 °C for 12 h to remove all moisture and ethanol, thus obtaining nano starch, denoted as SNPs.

[0026] Silane-modified nano starch SNPs-O and polyethylene glycol-modified nano starch SNPs-P are graft-modified nano starches.

[0027] The preparation method of silane-modified nano starch SNPs-O is as follows.

[0028] Starch was dried at 60 °C for 12 hours to remove moisture, then dispersed in anhydrous ethanol and sonicated for 30 minutes to activate hydroxyl groups. Octadecyltrimethoxysilane ODS (2% starch mass) was dissolved in ethanol / water (9:1), acetic acid was added to adjust the pH to 4-5, and the mixture was magnetically stirred at 60 °C for 30 minutes to generate silanol. This silanol was added to the starch suspension and reacted at 80 °C under nitrogen protection for 6 hours, maintaining the pH at 4-5.

[0029] After cooling to room temperature, the obtained starch was subjected to multiple ultrasonic centrifugations with ethanol to remove the remaining solvent and a small amount of soluble starch. Then, it was placed in a vacuum oven at 50 °C for 12 h to remove all moisture and ethanol, thus obtaining ODS modified nano starch, denoted as SNPs-O.

[0030] The chemical reaction formula is: .

[0031] The preparation method of polyethylene glycol modified nano starch SNPs-P is as follows.

[0032] Starch was dispersed in water, and 20% (starch mass fraction) sodium periodate (NaIO4) was added. The mixture was stirred at 25 °C for 6 hours to generate aldehyde-modified starch. The obtained starch was subjected to multiple ultrasonic centrifugations with ethanol to remove the residual solvent and a small amount of soluble starch, and then cooled and dried. The aldehyde-modified starch, PEG-20000, and DMSO were mixed in a ratio of 1:1:10 to prepare a reaction solution. 10% (starch mass fraction) citric acid was added, and the mixture was reacted at 80 °C for 4 hours under nitrogen atmosphere. Free PEG was removed, and the mixture was freeze-dried to obtain PEG-modified nano starch, denoted as SNPs-P.

[0033] The chemical reaction formula is: .

[0034] Starch TPSNPs-O / TPSNPs-P is thermoplastic starch formed by plasticizing starch SNPs-O / SNPs-P.

[0035] The preparation method of starch TPSNPs-O is as follows.

[0036] (1) Dry the starch SNPs-O at 60-80 ℃ until the moisture content is <5%.

[0037] (2) Mix starch SNPs-O and plasticizers (glycerol, sorbitol, citrate, etc.) evenly in a high-speed mixer.

[0038] (3) The material is melt-blended by a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, starch TPSNPs-O (SNPs-O→TPSNPs-O) is obtained. The thermoplastic starch TPS is prepared from natural starch.

[0039] The preparation method of starch TPSNPs-P is as follows.

[0040] (1) Dry the starch SNPs-P at 60-80 ℃ until the moisture content is <5%.

[0041] (2) Mix starch SNPs-P and plasticizers (glycerol, sorbitol, citrate, etc.) evenly in a high-speed mixer.

[0042] (3) The material is melt-blended by a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, starch TPSNPs-P (SNPs-P→TPSNPs-P) is obtained.

[0043] Example 2 A method for preparing a highly filled nano-starch modified PHB material, used to prepare the highly filled nano-starch modified PHB material in Example 1, specifically includes: (1) Weigh and dry the PHB resin, modified starch based on natural potato starch, main antioxidant and auxiliary antioxidant according to the ratio; the modified starch based on natural potato starch is at least one of nano starch SNPs, silane modified nano starch SNPs-O, plasticized starch TPSNPs-O, polyethylene glycol modified nano starch SNPs-P and plasticized starch TPSNPs-P.

[0044] (2) The dried raw materials in step (1) are mixed and continuously and evenly added to the main feed cylinder of the twin-screw extruder. The extruded strip is cooled by a water tank and then granulated to obtain the high-filled nano starch modified PHB material.

[0045] The twin-screw extruder has a rotational speed of 350-500 rpm, a screw diameter of 30-65 mm, and a length-to-diameter ratio (L / D) of 25-28.

[0046] The temperatures of the conveying section, melting section, mixing section, homogenizing section, and die section of the twin-screw extruder are 140-150 ℃, 150-165 ℃, 155-175 ℃, 150-160 ℃, and 145-155 ℃, respectively.

[0047] Example 3 A highly filled nano-starch modified PHB material comprises: 70-90 parts by weight of PHB resin, 10-30 parts by weight of starch Starch / SNPs / SNPs-O / SNPs-P / TPSNPs-P / TPSNPs-P, 0.1-0.5 parts by weight of primary antioxidant, and 0.1-0.5 parts by weight of secondary antioxidant.

[0048] Furthermore, under test conditions of 180 °C and 2.16 kg, the melt flow rate of PHB resin was 1-10 g / 10 min.

[0049] Specifically, in this embodiment, the raw materials used are as follows: PHB resin: PHB-1001MD, produced by BASF, Germany; natural potato starch: Shandong World Chemical Co., Ltd.; main antioxidant 1010: hindered phenolic antioxidant; auxiliary antioxidant 168: phosphite auxiliary antioxidant.

[0050] Using the above-mentioned raw materials, different proportions were selected to prepare highly filled nano-starch modified PHB materials. The specific formulations of different experimental groups and comparative proportions are shown in Table 1.

[0051] Table 1: Formulations of highly filled nano-starch modified PHB materials in different experimental groups .

[0052] The particle material prepared according to the method disclosed in Example 1 was dried in a forced-air oven at 80 °C for 3 to 5 hours, and then the dried particle material was injection molded into GB / T standard strips and color plates at an injection temperature of 180 °C. The performance of the injection molded strips was tested after being placed at 50% relative humidity and 23 °C for 48 hours.

[0053] Melt flow rate test: conducted according to GB / T 3682.1-2018 standard, plastic particles, 180 ℃, 2.16 kg.

[0054] Tensile strength test: conducted according to GB / T 1040.1-2018 standard.

[0055] Bending strength test: conducted in accordance with GB / T 9341-2008 standard.

[0056] Notched impact strength test of cantilever beam: conducted according to GB / T 1843-2008 standard.

[0057] The mechanical properties of materials are evaluated by measuring the tensile strength, bending strength, and notched impact strength of cantilever beams obtained from tests.

[0058] Contact angle test: performed according to ISO 19403-2:2017 standard.

[0059] Water absorption test: conducted according to GB / T 1034-2008 standard.

[0060] Biodegradability: Tested according to GB / T 19277.1 standard.

[0061] Performance tests were conducted according to the above standards, and the test results are shown in Table 2.

[0062] Table 2: Test Results .

[0063] A systematic analysis of the performance data of PHB and its composites allows for a deeper understanding of the impact mechanisms of different starch modification methods on material properties. In the nano-starch modified system of Experimental Group 1, the addition of 30 parts of nano-starch significantly increased the melt index from 0.5 (natural starch) to 23.8. This significant improvement in flowability stems from the small size effect and excellent dispersibility of nanoparticles, effectively reducing melt flow resistance. Regarding mechanical properties, nano-starch increased the tensile strength from 12 MPa to 28.8 MPa and the impact strength from 0.8 kJ / m² to 12.6 kJ / m². This strengthening effect is mainly attributed to the high specific surface area of ​​nanoparticles enhancing interfacial bonding. In terms of surface properties, the contact angle decreased from 54° to 50°, indicating that nanoscale dispersion increased the exposure of hydrophilic hydroxyl groups. Degradation performance remained excellent, with the degradation rate slightly increasing from 94% to 96%, thanks to the larger adhesion surface area provided by nano-starch for microorganisms.

[0064] As seen in experimental groups 2 and 3, PEG and ODS grafting exhibited drastically different characteristics in different grafting modification systems. The PEG-grafted system achieved an impact strength of 19.2 kJ / m², demonstrating the toughening effect of the PEG flexible segments, but its 6.5% water absorption rate and 56° contact angle indicated strong hydrophilicity. In contrast, the ODS-grafted system exhibited a superhydrophobic property of 105° and a water absorption rate of only 1.1%, attributed to the hydrophobic barrier formed by the octadecyl long chains. Its tensile strength of 39.6 MPa was also superior to that of the PEG-grafted system, but its impact strength decreased to 13.6 kJ / m², reflecting the restrictive effect of the silane cross-linking network on molecular chain movement. Regarding degradation performance, PEG grafting maintained a degradation rate of 92%, while ODS grafting decreased to 72%, confirming that the hydrophobic layer indeed delayed the microbial degradation process.

[0065] Experimental groups 4 and 5 involved the modification of thermoplastic starch. After plasticization with glycerol, the melt index of the PEG-grafted system increased from 20.2 to 33.2, and the impact strength increased from 19.2 to 23.8 kJ / m². This is a result of the glycerol plasticizer disrupting the hydrogen bonds between starch molecules. However, the flexural modulus decreased from 2090 MPa to 1805 MPa, indicating that while plasticization improves processing performance, it also reduces material rigidity. This modification method significantly improves the processing and performance of the material while maintaining a 90% degradation rate.

[0066] A comprehensive analysis of the performance of various formulations revealed that while natural starch exhibited a high degradation rate, it also had the worst mechanical properties. Nano-starch maintained a high degradation rate of 95% while significantly improving mechanical properties. The ODS-grafted system demonstrated the best hydrophobicity and high strength, but its degradation was slower. The PEG-grafted system exhibited the best toughness. These differences essentially stem from three key mechanisms: the nano-size effect improves dispersion by reducing particle size; surface chemical modification regulates interfacial properties through different functional groups; and plasticizing treatment affects material properties by altering molecular chain mobility. This performance regulation method based on the principle of material component interaction provides a scientific basis for the directional design of PHB composite materials.

[0067] The above embodiments are merely illustrative of the structural concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made based on the essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A highly filled nano-starch modified PHB material, characterized in that, The product comprises, by weight, 70-90 parts of PHB resin, 10-30 parts of modified starch based on natural potato starch, 0.1-0.5 parts of primary antioxidant, and 0.1-0.5 parts of secondary antioxidant. The PHB resin has a melt flow rate of 1-10 g / 10 min under test conditions of 180 ℃ × 2.16 kg, and the natural potato starch has a particle size of 30-50 μm.

2. The highly filled nano-starch modified PHB material according to claim 1, characterized in that, The modified starch is nano-sized starch SNPs, the particle size of the SNPs is less than or equal to 0.1 μm, and the preparation method of the SNPs includes: Step 1: Add natural potato starch and anhydrous ethanol to the grinding jar of a planetary ball mill at a ratio of 1:2, add 5% surfactant OP-10, fix the rotation speed at 300-500 r / min, control the temperature not to exceed 35 ℃, and the humidity not to exceed 40%; Step 2: The starch obtained in Step 1 is subjected to multiple ultrasonic centrifugations with ethanol to remove surfactants and soluble starch. Then, the ultrasonically centrifuged starch is placed in a vacuum oven at 50 °C for 12 h to remove all moisture and ethanol, thus obtaining nano-sized starch SNPs.

3. The highly filled nano-starch modified PHB material according to claim 2, characterized in that, The modified starch is silane-modified nano-starch SNPs-O, which is a grafted modified nano-starch. The preparation method includes the following steps: Step 3-1: Dry the nano-sized starch SNPs at 60 °C for 12 hours to remove moisture, then disperse them in anhydrous ethanol and sonicate for 30 minutes to activate the hydroxyl groups. Step 4-1: Dissolve 2% starch by weight of octadecyltrimethoxysilane ODS in 9:1 ethanol / water, add acetic acid to adjust the pH to 4-5, and magnetically stir at 60 °C for 30 minutes to generate silanol; Step 5-1: Add silanol to the starch suspension and react for 6 hours under nitrogen protection at 80 °C, maintaining the pH at 4-5. Cool to room temperature and perform multiple ultrasonic centrifugations on the obtained starch with ethanol to remove the remaining solvent and a small amount of soluble starch. Then place it in a vacuum oven at 50 °C for 12 hours to remove all moisture and ethanol, thus obtaining silane-modified nano starch SNPs-O.

4. The highly filled nano-starch modified PHB material according to claim 3, characterized in that, The modified starch is plasticized starch TPSNPs-O, which is a thermoplastic starch obtained by plasticizing silane-modified nano starch SNPs-O. The preparation method includes: Step 6-1: Dry the silane-modified nano starch SNPs-O at 60-80 ℃ until the moisture content is <5%; Step 7-1: Mix the dried silane-modified nano starch SNPs-O and plasticizer evenly in a high-speed mixer; Step 8-1: The material is melt-blended using a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, plasticized starch TPSNPs-O is obtained.

5. The highly filled nano-starch modified PHB material according to claim 2, characterized in that, The modified starch is polyethylene glycol-modified nano starch SNPs-P, which is a grafted modified nano starch. The preparation method includes the following steps: Step 3-2: Disperse nano-sized starch SNPs in water, add sodium periodate (NaIO4) with a starch mass fraction of 20%, and stir at 25°C for 6 hours to generate aldehyde-modified starch; Step 4-2: The obtained aldehyde-modified starch is subjected to multiple ultrasonic centrifugations with ethanol to remove the remaining solvent and a small amount of soluble starch, and then cooled and dried. Step 5-2: Prepare a reaction solution by mixing aldehyde-modified starch after ultrasonic centrifugation, PEG-20000, and DMSO in a ratio of 1:1:

10. Add citric acid with a starch mass fraction of 10% and react at 80 °C for 4 hours under nitrogen atmosphere to remove free PEG. Freeze-dry to obtain polyethylene glycol modified nano starch SNPs-P.

6. The highly filled nano-starch modified PHB material according to claim 5, characterized in that, The modified starch is plasticized starch TPSNPs-P, which is a thermoplastic starch obtained by plasticizing polyethylene glycol-modified nano starch SNPs-P. The preparation method includes: Step 6-2: Dry the polyethylene glycol-modified nano starch SNPs-P at 60-80 ℃ until the moisture content is <5%; Step 7-2: Mix the dried starch SNPs-P and plasticizer evenly in a high-speed mixer; Step 8-2: The material is melt-blended using a twin-screw extruder at a temperature of 90-120 ℃ and under shear force to form a homogeneous material. After extrusion granulation, plasticized starch TPSNPs-P is obtained.

7. A method for preparing a highly filled nano-starch modified PHB material, characterized in that, Includes the following steps: Step a: Weigh and dry the PHB resin, modified starch based on natural potato starch, main antioxidant, and auxiliary antioxidant according to the specified ratio; Step b: After mixing the dried raw materials from step a, continuously and evenly add them to the main feed cylinder of the twin-screw extruder. After the extruded strip is cooled by a water tank, it is granulated to obtain highly filled nano-starch modified PHB material.

8. The preparation method of the highly filled nano-starch modified PHB material according to claim 7, characterized in that, The modified starch based on natural potato starch uses at least one of nano starch SNPs, silane-modified nano starch SNPs-O, plasticized starch TPSNPs-O, polyethylene glycol-modified nano starch SNPs-P, and plasticized starch TPSNPs-P.

9. The preparation method of the highly filled nano-starch modified PHB material according to claim 7, characterized in that, The twin-screw extruder has a rotational speed of 350-500 rpm, a screw diameter of 30-65 mm, and a length-to-diameter ratio (L / D) of 25-28.

10. The method for preparing the highly filled nano-starch modified PHB material according to claim 7, characterized in that, The temperatures of the conveying section, melting section, mixing section, homogenizing section, and die section of the twin-screw extruder are 140-150 ℃, 150-165 ℃, 155-175 ℃, 150-160 ℃, and 145-155 ℃, respectively.